Next-Generation Sequencing Identification and Characterization of MicroRNAs in Dwarfed Citrus Trees Infected With Citrus Dwarfing Viroid in High-Density Plantings - Dang, Tyler; Lavagi-Craddock, Irene; Bodaghi, Sohrab; Vidalakis, Georgios (Frontiers in Microbiology, 2021)
Citrus dwarfing viroid (CDVd) induces stunting on sweet orange trees (Citrus sinensis (L.) Osbeck), propagated on trifoliate orange rootstock (C. trifoliata (L.), syn. Poncirus trifoliata (L.) Raf.). MicroRNAs (miRNAs) are a class of non-coding small RNAs (sRNAs) that play important roles in the regulation of tree gene expression. To identify miRNAs in dwarfed citrus trees, grown in high-density plantings, and their response to CDVd infection, sRNA next-generation sequencing was performed on CDVd-infected and non-infected controls. A total of 1,290 and 628 miRNAs were identified in stem and root tissues, respectively, and among those, 60 were conserved in each of these two tissue types. Three conserved miRNAs (csi-miR479, csi-miR171b and csi-miR156) were significantly downregulated (adjusted p-value <0.05) in the stems of CDVd-infected trees compared to the non-infected controls. The three stem downregulated miRNAs are known to be involved in various physiological and developmental processes some of which may be related to the characteristic dwarfed phenotype displayed by CDVd-infected C. sinensis on C. trifoliata rootstock field trees. Only one miRNA (csi-miR535) was significantly downregulated in CDVd-infected roots and it was predicted to target genes controlling a wide range of cellular functions. Reverse transcription quantitative polymerase chain reaction analysis performed on selected miRNA targets validated the negative correlation between the expression levels of these targets and their corresponding miRNAs in CDVd-infected trees. Our results indicate that CDVd-responsive plant miRNAs play a role in regulating important citrus growth and developmental processes that may participate in the cellular changes leading to the observed citrus dwarf phenotype.